THE EFFORTS TO INCREASE KNOWLEDGE ABOUT BALANCED NUTRITION AT ELEMENTARY SCHOOL CHILDREN - Ratih Damayanti; Indah Lutfiya; Neffrety Nilamsari (Darmabakti Cendekia: Journal of Community Service and Engagements, 2019)
Background: The balanced  nutrition  paradigm is currently unknown  to  the  general public, especially school-age children. The old paradigm of four healthy five perfects is still taught in schools. Whereas in the new paradigm of balanced nutrition, in addition to the principle of nutrition that must be consumed in a balanced manner, there is another message that must be conveyed, namely physical activity at least 30 minutes every day, regular exercise, drinking 8 glasses of water a day, washing hands before and after eating and always monitor your weight. Purpose: This community service activity aims to improve balanced nutrition knowledge in elementary school age children. Method: The method of community service is through lectures and games for ice breaking so that the atmosphere becomes more fun. Results: Most of the students of SDN Kalisari 1 Surabaya were female (54%), 10 years old (62%), and parents had jobs in the “other” category namely construction workers, janitors and farm workers (38%). As many as 83% of students have breakfast habits and 88% of students often access the internet. The level of student’s knowledge of balanced nutrition is included in the sufficient category (59%). There is a difference in the level of knowledge before and after counseling about the concept of balanced nutrition (α = 0.04). Conclusion: Efforts to increase knowledge of balanced nutrition with counseling and game methods are considered effective because there is a significant increase in the level of knowledge of SDN Kalisari 1 Surabaya students.